FUNDAMENTALISME ISLAM - Dwi Ratnasari (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2010)
The mindsets in understanding the teaching of a religion vary greatly among individuals or group of people,which are influenced by their prominent figures and books they read. As a result, conservative, moderate, and liberalmindsets can be found in society. In the last few years, people were surprised by the emergence of religious groups,especially in Islam, which tend to be conservative, irrational, and often using violence to defend their belief. Thisphenomenon seems to be the opposite of this modern era which tries to promote freedom in religion and behavior. Thisarticle discusses the history of the term